2015
DOI: 10.1016/j.euprot.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight peptides derived from sarcoplasmic proteins produced by an autochthonous starter culture in a beaker sausage model

Abstract: a b s t r a c tThis study focuses on meat protein degradation by different starter cultures. Sausage models inoculated with Lactobacillus curvatus CRL705 and Staphylococcus vitulinus GV318 alone and as a mixture were incubated 10 days at 22 • C. Low molecular weight peptides (<3 kDa) derived from sarcoplasmic proteins were analyzed by a peptidomic approach. A diverse number of protein fragments were identified. The greatest peptides diversity was obtained when the mixed starter culture was present. Peptides ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 55 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…For instance, S. vitulinus can be applied to break down myofibrillar proteins in fermented meat (López et al . ), whereas strains of S. xylosus and S. saprophyticus exhibit proteolytic and lipolytic activities in fermented fish (Zeng et al . ).…”
Section: Opportunitiesmentioning
confidence: 99%
“…For instance, S. vitulinus can be applied to break down myofibrillar proteins in fermented meat (López et al . ), whereas strains of S. xylosus and S. saprophyticus exhibit proteolytic and lipolytic activities in fermented fish (Zeng et al . ).…”
Section: Opportunitiesmentioning
confidence: 99%
“…The fourth sample with 55% of sodium reduction was manufactured in the meat processing plant (sample 580), with 3 replications (independent salami processing), using the following meat ingredients: pork shoulder (60%), beef chuck (20%) and pork back fat (20%), together with the following nonmeat ingredients: sodium nitrate (0.015%), sodium nitrite (0.015%), sodium erythorbate (1.0%), dextrose (0.75%) and spices (0.32%), based on 100% raw meat. Based on previous studies López et al (2015aLópez et al ( , 2015b selected autochthonous starter cultures (Enterococcus mundtii CRL 35, Staphylococcus vitulinus GV 318 and Lactobacillus sakei CRL 1862) isolated from an artisanal fermented sausage of Tucumán -Argentina, provided by Centro de Referencia para Lactobacilos (CERELA) were added at a concentration of 8 log CFU/g of starter cultures. The salami was processed in the following stages: firstly, the meat was minced using discs with holes of 10, 8 and 5 mm for pork, beef and pork back fat, respectively.…”
Section: Samplesmentioning
confidence: 99%
“…This caused by the reduction in NaCl, developing a bitter and metallic taste, which in turn is caused by the addition of salt substitutes (Aaslyng et al, 2014;Desmond, 2006;dos Santos et al, 2015). A strategy to mask the sensory characteristics generated by the addition of substitute salts is the addition of starter cultures, because it helps in obtaining low molecular weight (LMW) peptides on fermented meat products, enhancing the texture, color and flavor (López et al, 2015a;2015b). On the other hand (Behrens et al, 2007 andJaeger, 2006) reported that the foods perception is affected by intrinsic factors such as taste, odor, texture, among others, which play a fundamental role in the acceptance and purchase intention of the product by consumers.…”
Section: Introductionmentioning
confidence: 99%
“…The breakdown of proteins to peptides and amino acids is caused by the biochemical processes occurring during the process of marination and ripening, where the exogenous and endogenous enzymes are directly involved in the hydrolysis of proteins. Castellano et al [20] and López et al [21] reported that peptides are partly produced by the hydrolysis of the meat protein caused by the microbial enzymes. Rzepkowska et al [5] showed that organic acid whey contains a greater number of microorganisms, among which LAB, and especially Lactobacillus strains, were the predominant microflora.…”
Section: Discussionmentioning
confidence: 99%